Prototype Development of RFID-Based Truck Load Data Collection Tool with Smart Calibration and HMI Methods - Muhammad Erik Ardiansyah; Denny Irawan (LPPM Universitas Dian Nuswantoro, 2026)
With the advancement of technology, humans are also required to adapt to these advancements. The industrial sector is one sector significantly impacted by this technological development, from increasingly sophisticated production machines to increasingly flexible attendance systems for employees. However, amidst this technological advancement, the author found several aspects impractical in its application. One example is the use of paper documents for loading and unloading trucks. The use of paper documents can complicate the loading and unloading process, as paper documents have several weaknesses, such as water fading, tearing, forgery, and other weaknesses not included in this study. Based on these issues, the researcher taking the initiative to create a prototype of an RFID-based truck load data collection tool with smart calibration and HMI that facilitates truck drivers and warehouse personnel in the loading and unloading process. The system researcher designed consists of an RFID sensor connected to an Haiwell Scada. Keywords - Paper, RFID, Prototype, smart calibration, HMI, Truck